Dissociable glucocorticoid and noradrenergic effects on parochial cooperation and competition in intergroup conflict - Damon Dashti; Luca M. Lüpken; Mohammad Seidisarouei; Paul A. G. Forbes; Alfons Schnitzler; Tobias Kalenscher (Proceedings of the National Academy of Sciences, 2025)
Stress changes social behavior, yet its effects remain contradictory. Traditionally, stress was thought to trigger an antagonistic fight-or-flight response aimed at eliminating the stressor. However, recent studies have revealed the opposite response, tend-and-befriend, where individuals prosocially invest in their social network in exchange for support and mutual protection. We hypothesize that stress does not promote one response over the other; instead, it stimulates both behaviors, dissociable on the neuropharmacological level and moderated by social context. In a placebo-controlled, double-blind psychopharmacological study, we administered hydrocortisone and yohimbine—alone or in combination—to manipulate the actions of the main stress hormone cortisol and the arousal transmitter noradrenaline. Participants then made decisions in an intergroup conflict task. They teamed up with others to form an in-group and played against multiple out-groups. Notably, out-group members initiated financial harm to in-group participants before these responded. Participants then chose either to 1) maximize their own payoff, 2) cooperatively increase the payoff of their in-group, or 3) increase the in-group’s payoff while competitively decreasing that of the out-group. Consistent with our hypotheses, glucocorticoid activation increased generosity toward the in-group, whereas noradrenergic activation increased parochial competition, i.e., prosocial in-group support combined with hostility toward the out-group. These findings challenge the dichotomy between fight-or-flight and tend-and-befriend, suggesting stress-related behavior is neither static nor one-directional, but shaped by the relative dominance of cortisol versus noradrenaline in the neurohormonal stress response and by intergroup dynamics. We highlight broader societal implications, offering a potential biological mechanism underlying the self-perpetuating cycle of intergroup conflict.